24 Y‐chromosomal STR haplotypic polymorphisms for Chinese Uygur ethnic group and its phylogenic analysis with other Chinese groups. Issue 4 (23rd January 2015) - Liu, Wen‐Juan; Pu, Hong‐Wei; Yang, Chun‐hua; Meng, Hao‐Tian; Zhang, Yu‐Dang; Zhang, Li‐Ping; Yan, Jiang‐Wei; Wang, Hong‐Dan; Ren, Jian‐Wen; Sun, Jun‐Yi; Liu, Chao; Wang, Hui; et al.
<x xml:space="preserve">Abstract</x> The Uygur ethnic minority is the largest ethnic group in the Xinjiang Uygur Autonomous Region of China, and is a precious resource for the study of ethnogeny and forensic biology. Previous studies have focused on the genetic background of the Uygur group, however, the patrilineal descent of the group is still unclear. In this study, we investigated the genetic diversity of 24 Y‐STR loci in the Uygur group and analyzed the population differentiations as well as the genetic relationships between the Uygur group and other previously reported populations using 17 Y‐filer loci. According to haplotypic analysis of the 24 Y‐STR loci in 109 Uygur individuals, 104 different haplotypes were obtained, 99 of which were unique. The haplotypic diversity and discrimination capacity of these 24 Y‐STR loci in Uygur group were 0.9992 and 0.9541, respectively. An additional 7 loci (DYS388, DYS444, DYS447, DYS449, DYS522, and DYS527a, b) showed high genetic diversity and improved the overall discrimination capacity of the 24 Y‐STR system. Pairwise Fst and neighbor‐joining analysis showed that the Uygur group was genetically close to the Han populations from different regions.